The Flexibility of Pusher Furnace Grate - Słowik J.A.; Drotlew A.; Piekarski B. (Archives of Foundry Engineering, 2016)
The lifetime of guide grates in pusher furnaces for heat treatment could be increased by raising the flexibility of their structure through, for example, the replacement of straight ribs, parallel to the direction of grate movement, with more flexible segments. The deformability of grates with flexible segments arranged in two orientations, i.e. crosswise (perpendicular to the direction of compression) and lengthwise (parallel to the direction of compression), was examined. The compression process was simulated using SolidWorks Simulation program. Relevant regression equations were also derived describing the dependence of force inducing the grate deformation by 0.25 mm ‒ modulus of grate elasticity ‒ on the number of flexible segments in established orientations. These calculations were made in Statistica and Scilab programs. It has been demonstrated that, with the same number of segments, the crosswise orientation of flexible segments increases the grate structure flexibility in a more efficient way than the lengthwise orientation. It has also been proved that a crucial effect on the grate flexibility has only the quantity and orientation of segments (crosswise / lengthwise), while the exact position of segments changes the grate flexibility by less than 1%.